2009
DOI: 10.1002/app.30729
|View full text |Cite
|
Sign up to set email alerts
|

Conductive network formation and electrical properties of poly(vinylidene fluoride)/multiwalled carbon nanotube composites: Percolation and dynamic percolation

Abstract: Conductive network formation and its dynamic process for multiwalled carbon nanotubes (MWNTs) and carboxyl-tethered MWNT (MWNT-COOH) filled poly(vinylidene fluoride)(PVDF) systems were investigated. Based on real-time tracing the variation of electrical resistivity of systems with isothermal treatment time, the conductive network formation was evaluated. It was found that the conductive network formation was temperature and time dependent. The percolation time, characterized at a certain annealing time where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Further, in the same article, the storage modulus of the PC/MWCNTs was also investigated as a function of aspect ratio, and the results indicate that the rubbery moduli at 180 and 200 °C both increase with increasing the aspect ratio of MWCNTs . Other studies have also indicated that the diameter and length of CNTs (either single‐walled or multi‐walled CNTs), as well as degree of functionality on the CNTs, have great influences on the electrical conductivity, mechanical properties, and thermal properties of polymer/CNT composites.…”
Section: Introductionmentioning
confidence: 93%
“…Further, in the same article, the storage modulus of the PC/MWCNTs was also investigated as a function of aspect ratio, and the results indicate that the rubbery moduli at 180 and 200 °C both increase with increasing the aspect ratio of MWCNTs . Other studies have also indicated that the diameter and length of CNTs (either single‐walled or multi‐walled CNTs), as well as degree of functionality on the CNTs, have great influences on the electrical conductivity, mechanical properties, and thermal properties of polymer/CNT composites.…”
Section: Introductionmentioning
confidence: 93%
“…High temperature enhances the diffusion constant of the medium and Brownian motion, reducing the amount of time needed to reduce the orientation imparted to CNTs during the initial molding and to form an electrically conductive nanotube network in the solid. [ 23, 30–32].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to better understand the variation of activation energy in CPCs with different fillers, activation‐energy values calculated by the percolation time and zero‐shear viscosity are plotted to compare with some results reported in the literature (Figure ) . Those results further indicate that the filler types, such as filler geometry and surface polarity, greatly affect the activation‐energy values …”
Section: Resultsmentioning
confidence: 76%